Entrepreneurial Intentions and Adaptability of Senior High School (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Entrepreneurial intentions reflect an individual's drive and readiness to engage in entrepreneurial activities or start their own business ventures, while adaptability refers to the capacity to adjust to changing business environments, essential for entrepreneurs to achieve productive employment and decent work in the future. The researchers observed that students show a hint of interest in taking an entrepreneurial career, but they are also hesitant to pursue it. Thus, this study aimed to explore the entrepreneurial intentions and adaptability of the students. Through quantitative descriptive-correlational design, the researchers surveyed 161 senior high school students chosen using simple random sampling. The level of entrepreneurial intentions and adaptability were treated using weighted mean and standard deviation, while the significant relationship between the variables was determined using Pearson Product Moment Correlation. The findings reveal that the respondents exhibit high entrepreneurial intentions driven by factors such as motivation, personal interest, and social support, despite some concerns about financial risks. They also demonstrate a high level of adaptability, showing resilience and problem-solving skills in response to changes in the business environment. However, there is still a need to further develop these aspects since there are still rooms for improvement. Strong significant correlation was also found between the two, indicating that a higher entrepreneurial intention leads to higher adaptability, and vice versa. The researchers recommend strengthening the entrepreneurship learning experiences of students, and conducting training to boost their interest in entrepreneurship, and make them more resilient in the business landscape.
Keywords: entrepreneurial intentions; entrepreneurial adaptability; entrepreneurship